PCR-Based Detection of Genetically Modified Soybean and Maize in Raw and Highly Processed Foodstuffs - C. Tengel; P. Schüßler; E. Setzke; J. Balles; M. Sprenger-Haußels (BioTechniques)
The PCR method has proved to be an invaluable tool for the specific and sensitive detection of genetically modified material (e.g., Roundup Ready™ Soybean and Bt-176 “Maximizer” Maize) in foodstuffs. The first step in the procedure, namely the purification of nucleic acids from the sample, is often the deciding factor in the production of meaningful results. In this study, we present two procedures that enable an efficient isolation of trace amounts of genetic material from both raw and highly processed foodstuffs. We show that for optimal, PCR-ready DNA purification from highly processed foodstuffs and PCR inhibitor-rich substances—such as cocoa-containing products—adapted protocols for the QIAGEN® QIAamp® DNA Stool Mini Kit can be utilized. For complete DNA isolation from raw foodstuffs, a protocol using the DNeasy® Plant Mini Kit is presented.